Smartex Sdn Bhd / Nur Hanis Fitriah Mohd Hasni ... [et al.] - Nur Hanis Fitriah, Mohd Hasni; Rishafeeka, Mohd Shah; Nurul Eirna Farhana, Mohamad Izam; Fiqah, Muzi; Aida Shada, Shamsulbahri (2019)
Based on the previous business opportunities that we have carried out, we have chosen one business opportunity to be taken into a business idea. The business plan is to produce the Smart Basket and Smart Cash Machine and turns it into a high technology company. From these business plan, we have laid out some of the flows of the business such as the marketing plan, administration management, financial plan and also the operational plan in order to project a functional and efficient company system along in maintaining its image as a modem and versatile technology company. The idea of establishing this company has been taken into deep consideration to ensure that only the finest products are being manufactured and sold. The products are being produced based on customer's needs and also client's demand in achieving the fast checkout and minimizing the lagging payment during shopping. In addition, the products are not only boasting the financial economy, but they are also expanding the creativity to create and produce something new that may be or may be not in the market yet. This business is indeed an eye-opening to the technology world as it is a new technology in the market and lift up the image of this country too.